THE ROLE OF FINANCIAL DEVELOPMENT AND INSTITUTIONAL QUALITY ON ENVIRONMENTAL SUSTAINABILITY IN SUB-SAHARAN AFRICAN COUNTRIES - Jibrilla, Aliyu Alhaji (International Journal of Research -GRANTHAALAYAH, 2018)
This study addresses the question of financial development and institutional quality influence on the environmental sustainability of some 13 countries from the sub-Saharan Africa. Relying upon pooled mean group (PMG) for panel data, we provide evidence which suggest that both financial development and institutional quality are statistically significant determinants of per capita carbon dioxide emissions in the region. More specifically, we found that without healthy institutions and sound financial system sub-Saharan African countries might not avoid environmental degradation experienced by advanced nations during their early stage of economic progress. Our results also support the EKC hypothesis in the region. In addition, the paper also shows that more openness to FDI inflows is good for the environment across the SSA. These findings suggest the need for institutional and financial service reform that supports robust environmental conservation.